Al-Qadi Abd Al-Jabbar: Suatu Biografi - Mohd Radhi Ibrahim (Bahagian Pengajian Usuluddin Akademi Pengajian Islam Universiti Malaya, 2024)
The aim of this article is to introduce al-Qadi' Abd al-Jabbar's background as one of the most prominent Islamic Rationalists of his time and his contributions to Islamic Intellectual Heritage.